Low Voltage Ride-Through Capability of Three-Phase PV System Connected to Low-Voltage Grid by Using Adaptive PR Controller - Bhunia J.; Kumar J.; Mukherjee D. (My University, 2025)
In this paper low voltage ride-through capability of the three-phase PV system connected to low-voltage grid by using a non-ideal Proportional-Resonant (PR) controller has been studied according to the Indian grid code (Central Electricity Authority of India) and also to ensure the power quality, selective Harmonic Compensator (HC) has been used along with the current controller. To meet the increasing demand of load, integration of renewable energy to the grid becomes frequent and at the same time, Renewable Energy Sources (RES) must follow the various grid codes for maintaining the system stability as well as to enhance the robustness of the system. The Low Voltage Ride Through (LVRT) is one of the important grid codes and the purpose of LVRT scheme is to inject reactive power into the grid to recover the voltage of the grid when the voltage of the grid becomes less than the specified value. In this proposed control technique, there are two modes of operation, MPPT operation mode and LVRT or non-MPPT operation. The main reasons for the voltage sag are the fault or the high reactive power absorption by the load on the distribution side. In this paper, the symmetrical fault is considered to study LVRT operation. The simulation results of the 100 kW grid-connected PV system show that the proposed LVRT scheme improves the dynamic performance of the PV system and also effectively controls the DC-link capacitor voltage during the LVRT operation. © 2021 IEEE.